Equations of state implementation for 1–D modelling of performance in ram accelerator thermally choked propulsion mode. (10th April 2015) - Bauer, Pascal; Bengherbia, Tarek; Knowlen, Carl; Bruckner, Adam; Yao, Yufeng; Giraud, Marc
This paper presents advancement on one–dimensional (1–D) unsteady modelling of a ram accelerator (RAMAC) in the sub–detonative velocity regime by including real–gas equations of state (EoS) in order to account for the compressibility effects of the combustion products. Several equations of state based on generalised empirical and theoretical considerations are incorporated into a 1–D computer code TARAM. The objective of this work is to provide the best available formulations in order to improve the unsteady 1–D model and make the TARAM code a useful tool to predict the performance of the RAMAC in the sub–detonative velocity regime, without having to resort to more complicated 2–D or 3–D computational schemes. The calculations are validated against experimental data from 38–mm and 90–mm–bore facilities and good agreements have been achieved. Yet, the results demonstrate the need for further CFD studies involving the scale effect.